Physical training with increasing workload for chronic heart failure patients - the influence on left ventricular parameters - Klecha, Artur (2005)
Chronic heart failure due to its incidence and unfavorable prognosis is an increasingly important clinical, epdemiological and economic problem. Despite progress in pharmacological and invasive treatment the outcomes are still unsatisfactory and long-term prognosis is poor. Physical training is a well-known complementary modality in the treatment of chronic heart failure, however many aspects require further studies. One of them is the impact on myocardial morphology and function. Available evidence shows that physical training modifies the failing heart. The purpose of the present study was to evaluate the effect of out-patient 6-month physical training on left ventricle, exercise capacity, skeletal muscle metabolism in lower extremities and safety issues in patients with chronic ischemic heart failure. Material and Methods: the study was conducted in 50 patients (38 men, 12 women, man age 60.1±9.2 years) with chronic ischemic heart failure NYHA class II and III and left ventricular ejection fraction < 35%. The entry criterion was clinical stabilization on standard treatment at least 6 weeks prior to the study. All patients received a beta-blocker (carvedilol) and ACE inhibitor (lisinopril) in the highest tolerated doses. Drugs from other classes were used optionally. The patients, according to place of residence, were divided into two groups: undergoing 6-month physical tr
Keywords: cardiac magnetic resonance; left ventricle; physical training